Protein Turnover in Skeletal Muscle: Looking at Molecular Regulation towards an Active Lifestyle - Ferreira, Rita Pinho; Duarte, Jose Alberto (International Journal of Sports Medicine, 2023)
Skeletal muscle is a highly plastic tissue, able to change its mass and functional properties in response to several stimuli. Skeletal muscle mass is influenced by the balance between protein synthesis and breakdown, which is regulated by several signaling pathways. The relative contribution of Akt/mTOR signaling, ubiquitin-proteasome pathway, autophagy among other signaling pathways to protein turnover and, therefore, to skeletal muscle mass, differs depending on the wasting or loading condition and muscle type. By modulating mitochondria biogenesis, PGC-1α has a major role in the cell’s bioenergetic status and, thus, on protein turnover. In fact, rates of protein turnover regulate differently the levels of distinct protein classes in response to atrophic or hypertrophic stimuli. Mitochondrial protein turnover rates may be enhanced in wasting conditions, whereas the increased turnover of myofibrillar proteins triggers muscle mass gain. The present review aims to update the knowledge on the molecular pathways implicated in the regulation of protein turnover in skeletal muscle, focusing on how distinct muscle proteins may be modulated by lifestyle interventions with emphasis on exercise training. The comprehensive analysis of the anabolic effects of exercise programs will pave the way to the tailored management of muscle wasting conditions.
Keywords: protein synthesis; proteolysis; mitochondrial homeostasis; signaling; exercise training